2008
DOI: 10.2166/wst.2008.650
|View full text |Cite
|
Sign up to set email alerts
|

Biomass adaptation to complex substrate degradation in membrane bioreactors: appropriated operating conditions

Abstract: The aim of this work is to analyse the biological performances of two immersed membranes bioreactors focusing on the biomass adaptation to complex substrate degradation and the performance in term of permeate quality. Two influents were selected: a synthetic complex influent (acetate/Viandox, MBR1) and a real seafood processing wastewater (surimi product, MBR2). The MBR systems were operated for long periods without any sludge extraction except for sampling. Organic matter removal, sludge production and qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…In this 5MBR stalked ciliates were found higher than free swimming ones and only a few Suctoria or Rotifer. These microhials indicated and confirmed that the stahility of studied 5MBR was well performed whatever the permeation of flux values tested [8][9].…”
Section: Sludge Characteristicssupporting
confidence: 77%
See 2 more Smart Citations
“…In this 5MBR stalked ciliates were found higher than free swimming ones and only a few Suctoria or Rotifer. These microhials indicated and confirmed that the stahility of studied 5MBR was well performed whatever the permeation of flux values tested [8][9].…”
Section: Sludge Characteristicssupporting
confidence: 77%
“…The SVI value was measured and its values reported. to he ahout 103-108 ml/g, This range of SVI values showed the good settling characteristic of sludge that may he expected in the 5MBR, even if the system was not operating for a long enough period of time [8][9]. This result clearly showed that the sludge characteristics ohtained from a short term operation of 30-35 days can represent that of a long term operation as in general AS.…”
Section: Sludge Characteristicsmentioning
confidence: 57%
See 1 more Smart Citation
“…A submerged MBR system successfully treated seafood waste under a range of COD, suspended solids, and saline loadings. Soluble microbial products were found to be the principal fouling agent (Sridang et al, 2008a).…”
Section: Seafoodmentioning
confidence: 99%